A study of association between serum zinc and HbA1c in type2 diabetic patients in a tertiary care hospital in Puducherry, Tamilnadu - Seetharaman, Dhanoushyaa; Perumal, Muraliswaran; Mohan, Priyatharshini; Gnanasekaran, Prabu; Venkatesan, Indhumathi (Asian Journal of Medical Sciences, 2021)
Background: Diabetes currently affects more than 66.8 million people in India which has become a major health care problem, representing the largest number of any country in the world. Reduced concomitant intake of Zinc studies proved to be associated with risk of increased HbA1c percentage in individuals with Type 2 Diabetes patients. Aims and Objective: The current study was designed to assess serum Zinc level in Type 2 Diabetes patients and to find out the correlation between serum Zinc and HbA1c level in Type 2 Diabetic patients. Materials and Methods: One hundred patients were included in the study and they were divided into two groups like Group I (50 patients): Type 2 Diabetic patients with HbA1c more than 7 percent. Group II (50 patients): Type 2 Diabetic patients with HbA1c less than 7 percent (50). Estimation of blood glucose (Fasting and post prandial), Glycated haemoglobin (HbA1c) and serum Zinc was done. Statistical Analysis: The data is collected, recorded and analyzed statistically to determine the significance of different parameters by using SPSS package for windows version23.0. Results: The mean value of serum zinc was lower in the diabetic group whose HbA1c more than 7 (p value – 0.001) when compared to the diabetic group whose HbA1c less than 7. Conclusion: Estimating the level of serum zinc becomes important to know the status of insulin in diabetic patients and correlating the levels of HbA1c and Serum zinc in Type 2 DM patients, can monitor the levels of glycemic control and prevent the risk of development of complications.